PENGARUH LIKUIDITAS, WAKTU JATUH TEMPO, DAN KUPON TERHADAP PERUBAHAN HARGA OBLIGASI KORPORASI DI BEI - Savitri Karina Anandasari, Luh Putu; Sudjarni, Luh Komang (E-Jurnal Manajemen, 2017)
Companies in the operations require a certain amount of funds to achieve goals. Sources of funding needed one of which comes from long-term debt including bond debt. Bondholders should pay attention to bond price change in investing in bonds. Bond price change was influenced by liquidity, maturity and coupon, so the purpose of this study was determine effect of liquidity, maturity and coupon to corporate bond price change. The research was conducted on IDX. In this research the data is secondary obtained from IDX, IBPA, and TICMI. The number of samples is 57 bonds, using purposive sampling method. The analysis technique applied was multiple linear regressions and processing of data using IBM SPSS 21.0 for windows. Based on the analysis, the conclusion are liquidity have positive significant effect on bond price change. Maturities have negative significant effect on bond price change. Coupons have positive significant effect on bond price change.
Keywords: bond price change; liquidity; maturity; coupon